Jaina System of Knowledge Management A Comparative Study with Modern Knowledge Management System - Jain, Dr Alka (IJRDO -Journal of Computer Science Engineering, 2015)
Modern definitions of data, information and knowledge explain them in these words, “ and Data are unorganised and unprocessed fact.Information means shaping the data to arrive at a meaning in the eyes of the perceiver.Knowledge is human understanding of information based on its perceived importance or relevance to a problem area.” The author was able to find a sililar path of guidelines in Jaina Knowledge Management system and modern management system. Origin of Jaina KMS is at least 2500 years back while modern KMS is in its infancy stage yet. A comparative analysis of top attributes of both the KMS – one ancient and one modern, has been done in this study. Architecture in Jain literature and user Training in Jaina Agamic System has been studied. In Jaina KMS निक्षेप, प्रमाण and ज्ञाि etc. are the tools to know anything.Jain community has been treated as The Knowledge Organisation. Knowledge Creation and Knowledge Post system evaluation of the knowledge in Jainism is kaiwalya (Self realisation after gaining all the knowledge). According to Awad and Ghaziri, Knowledge Management system is developed to gather, organize, refine and distribute knowledge. This process takes place in Jaina Knowledge Management System through ‘स्वाध्याय, वाचिा,पच्ृछिा,अिुप्रेक्षा, धमम कथा etc. The comparison has been done by quoting modern management scholars and ancient Jaina scriptures like Uttradhyayan Sutra and Nandi Sutra. All the members of Jain Community have been treated as members of an organisation.In fact the whole coomunity is treated as an organisation.Then the theory of modern knowledge management system has been tested on Jain treasure of knowledge to verify that a sound knowledge management system used to exist and still exists in Jain community, which has helped in safety and security of the knowledge in its dispersion to other followers